2015
DOI: 10.5455/musbed.20150602011201
|View full text |Cite
|
Sign up to set email alerts
|

Family-oriented nursery approach to despair levels of the parents of children with cardiac disease and down syndrome

Abstract: Kalp hastalığı olan down sendromlu çocukların ebeveynlerinin umutsuzluk düzeylerine aile merkezli hemşirelik yaklaşımı Amaç: Araştırma kalp hastalığı olan down sendromlu çocuklara sahip ebeveynlerin umutsuzluk düzeylerine aile merkezli hemşirelik yaklaşımın etkisini değerlendirmek amacıyla deneysel olarak gerçekleştirilmiştir. Yöntem: İstanbul'da bir devlet hastanesinde Mart-Mayıs 2013 tarihleri arasında yapılan çalışma; çocuk kardiyoloji ve kardiyovasküler cerrahi servisinde yatan veya poliklinik kontrolüne g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…Akandere et al (25), Durat et al (26) and Yildirim & Yildirim (27) reported that parents who graduated from primary school had higher levels of hopelessness. Çatalbaş et al (28) reported that the hopelessness level of parents who received education was lower. The reason for the low level of hopelessness in parents with a high level of education may be that these parents have more information about their children's disease, treatment and care opportunities, and develop appropriate coping mechanisms and use problem-solving resources well in this process.…”
Section: Discussionmentioning
confidence: 99%
“…Akandere et al (25), Durat et al (26) and Yildirim & Yildirim (27) reported that parents who graduated from primary school had higher levels of hopelessness. Çatalbaş et al (28) reported that the hopelessness level of parents who received education was lower. The reason for the low level of hopelessness in parents with a high level of education may be that these parents have more information about their children's disease, treatment and care opportunities, and develop appropriate coping mechanisms and use problem-solving resources well in this process.…”
Section: Discussionmentioning
confidence: 99%
“…In the study, 64.6% of the sample group consisted of mothers. It was found that mothers were the most common caregivers in the studies which were conducted with the people who take care of their disabled children (Caicedo, 2014;Çatalbaş, Manav, & Ocakçı, 2015;Durat et al, 2017;Gürhopur & Dalgıç, 2017). Although the presence of a disabled child affects all family members, the primary caregiver mother is the most affected individual in this; process (Çalışır et al, 2018).…”
Section: Discussionmentioning
confidence: 99%